Antibacterial and antifungal property of three plants against oral microbes - Chandana Kalita; Ankumoni Saikia; Ajanta Sarma; Kasturi Saikia; Anjanamoyee Saikia; Anjan Kumar Saikia (Wolters Kluwer Medknow Publications, 2018)
Introduction: Use of medicinal plants to cure diseases has been practiced throughout the world. This is more common among the rural population as the reach of modern health-care facility is very little toward them. Rural population treats or manages different oral disease with the locally available herbs, which has been used traditionally. Among them, tulsi, neem, and Pochotia are most commonly used herbs in Assam. Aim: The aim of the study was to find out antibacterial and antifungal properties of Tulsi, Neem, and Posotia against few isolated oral microbes. Materials and Methods: Three commonly used plants - tulsi, neem, and Pochotia taken for antimicrobial study. Twigs dried and powdered and extract made with water and acetone. Microorganisms were isolated from the oral swab taken from the patient attending Out Patient Department of Regional Dental College, Guwahati. Antibacterial and antifungal potential of these plants was observed using agar well-diffusion method. Results: Tulsi and Pochotia showed antibacterial activity against Streptococcus mitis and Streptococcus viridans, whereas neem extract showed inhibitory effect against Klebsiella species. Neem and Pochotia showed antifungal action against Candida albican in both aqueous and acetone extract. The positive control of ciprofloxacin and itraconazole produced significant size of the inhibition zone. Statistical analysis was done using Instat Software. For comparing means, F-test was applied and considered P < 0.05 to be significant. Conclusion: Antimicrobial essay showed the antibacterial and antifungal action of these plants against oral microbes. It is important to identify and isolate the proper constituent responsible for this mechanism.